1986
DOI: 10.2307/1590535
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses Associated with Outbreaks of Transmissible Enteritis of Turkeys in Quebec: Hemagglutination Properties and Cell Cultivation

Abstract: Coronaviruses were observed by electron microscopy in the intestinal contents of turkeys in Quebec flocks where repeated outbreaks of enteritis occurred. Three isolates could be serially propagated in turkey embryos inoculated by the amniotic route with clarified intestinal contents. Purification and concentration of viral particles contained in intestinal contents of infected embryos were achieved by precipitation with polyethylene glycol and ultracentrifugation on sucrose density gradients. Three particle ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 8 publications
3
36
0
1
Order By: Relevance
“…The origin of the nine tissue culture-adapted Quebec strains of TCV, listed in Fig. 9, has been reported (Dea et al, 1986;Dea & Tijssen, 1988a).…”
Section: Cellsmentioning
confidence: 87%
See 2 more Smart Citations
“…The origin of the nine tissue culture-adapted Quebec strains of TCV, listed in Fig. 9, has been reported (Dea et al, 1986;Dea & Tijssen, 1988a).…”
Section: Cellsmentioning
confidence: 87%
“…The tests were done as described elsewhere (Dea et al, 1979(Dea et al, , 1986. The serum neutralization (SN) titre was expressed as the reciprocal of the highest serum or ascitic fluid dilution neutralizing 100 TCIDs0 of the virus.…”
Section: Turkey Enteric Coronavirus Mabsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integral membrane protein (M), which is largely embedded in the lipid bilayer targets the site of virus morphogenesis (Tooze et al, 1984) and may be implicated in viral pathogenesis (Fleming et al, 1989), whereas the bulbous peplomer (S) protein is responsible for virus binding (Cavanagh & Davis, 1986;Koch et al, 1990) as well as virulence and tissue tropism (Wege et al, 1988). An additional surface protein (HE), responsible for haemagglutination, has been found in bovine coronavirus (BCV; King et al, 1985;Hogue et al, 1989;Parker et al, 1989), human respiratory coronavirus strain OC43 (HCV-OC43; Hogue & Brian, 1985), haemagglutinating encephalitis virus of swine (Callebaut & Pensaert, 1980), diarrhoea virus of infant mice (Sugiyama et al, 1986) and turkey coronavirus (TCV; Dea et al, 1986). The HE protein of BCV also exhibits an acetyl esterase receptor-destroying activity similar to the activity found in influenza C viruses (Vlasak et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A hemagglutination-inhibition test showed that there was no antigenic relationship between TCoV and other animal coronaviruses involved with enteric problems and it was considered an easy and applicable serological test by Dea et al (1986). The tests of Pomeroy et al (1975) were not able to produce an inactivated vaccine against coronaviruses infections.…”
Section: Enteric Viruses In Turkey Flocks: a Historic Reviewmentioning
confidence: 99%